2019
DOI: 10.1186/s12917-018-1725-4
|View full text |Cite
|
Sign up to set email alerts
|

Predicting career sector intent and the theory of planned behaviour: survey findings from Australian veterinary science students

Abstract: BackgroundProducing graduates for a breadth of sectors is a priority for veterinary science programs. Undergraduate career intentions represent de-facto ‘outcome’ measures of admissions policy and curricula design, as intentions are strong predictors of eventual behaviour. Informed by Ajzen’s Theory of Planned Behaviour, this study aimed to identify if contextually relevant attitudes and self-ratings affect student intentions for veterinary career sectors.ResultsSurvey responses from 844 students enrolled in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
5
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 46 publications
(82 reference statements)
2
5
0
4
Order By: Relevance
“…The results of this study serve as guidelines for veterinary education policy makers in increasing knowledge innovation, recruitment of work midwives, and curriculum design. So that it can design better learning management (Feakes AM, et al, 2019). This research can be concluded that it is suitable and proven to be effective in implementing IL which includes an element of increasing the ability of students both academic and non-academic to realize a good career in the future.…”
Section: Discussionmentioning
confidence: 87%
“…The results of this study serve as guidelines for veterinary education policy makers in increasing knowledge innovation, recruitment of work midwives, and curriculum design. So that it can design better learning management (Feakes AM, et al, 2019). This research can be concluded that it is suitable and proven to be effective in implementing IL which includes an element of increasing the ability of students both academic and non-academic to realize a good career in the future.…”
Section: Discussionmentioning
confidence: 87%
“…Una de las prioridades de los programas de ciencias veterinarias es la preparación de graduados para una amplia gama de sectores (Feakes et al, 2019) . Entre ellos, la motivación de los estudiantes es muy alta cuando las actividades involucran la práctica clínica y el trabajo con animales (Parkinson et al, 2006).…”
unclassified
“…Las intenciones de los estudiantes de veterinaria son fuertes predictores de sus comportamientos futuros (Feakes et al, 2019). Aunque puede no perdurar por largo tiempo luego de graduados (Heath, 2007), la preferencia por los grandes animales productores de alimentos está asociada a las experiencias de los estudiantes previas al ingreso a la carrera (Lenarduzzi et al, 2009).…”
unclassified
See 2 more Smart Citations